The Role of Islamic Influencers in Shaping Attitudes Religious Tolerance Among Gen Z - Abidin, Muh. Mukhlish Abidin (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to analyze the role of da'wah influencers on social media in shaping attitudes of tolerance among Generation Z. The increasing role of influencers in shaping public opinion, including on religious issues, makes this research relevant in the context of religious moderation in the digital era. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews with 10 informants born in the 2000s who actively use social media. Informants were selected using a purposive sampling technique with selection criteria adjusted to the research needs. The results show that influencers play a significant role in shaping attitudes of religious tolerance among Generation Z. Moderate influencers, with their use of humanistic, educational, and dialogical narratives, are able to foster an open, inclusive attitude and respect for differences among their followers. Conversely, provocative influencers through their emotional, confrontational, and exclusive content actually strengthen the polarization of religious identities. However, despite this, the greatest influence is determined by the digital maturity of the audience and the ability of Generation Z social media users to critically sort information.